PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA RUMAH CANTIK SABINA BALIKPAPAN - Rosalina Mariska Putri, Dina; Prihandoyo, C.; Hermawansyah, Adi; Tangke Rante, Nely (Jurnal GeoEkonomi, 2024)
The Objective of the research to determine the effect of Service Quality on Customer satisfaction of Rumah Cantik Sabina Balikpapan which is motivated by the phenomenon of the  showing beauty clinics that offer a variety of beauty products and services, therefore in choosing a beauty clinic as a place for health care and skin beauty, good service quality will affect customer satisfaction.  One of this place is Rumah Cantik Sabina clinic in Balikpapan which complements healthy and beauty care and with the dynamic market condition, market players work extra to be able to win is very tight competitive market. This study was conducted on people who had finished doing of the  facial beauty treatment and had done facial beauty treatment at least twice.  The Sampling technique by non probability sampling. The analysis method used in this study was multiple linear regression and questionnaires as a tool for collecting respondent data and then processed with  the SPSS Statistic program with a sample number total of 238 respondents. The data analysis techniques used in this study are validity test, reliability test, partial test, r square determination coefficient test and simple linear regression analysis. The partial test is used to test the hypothesis, and the coefficient of determination test R square to see how much the independent variable affects the dependent variable. Based on the result of this research obtained from this study, service quality has a positive and significant influence on customer satisfaction at Rumah Cantik Sabina Balikpapan.  Service quality has an influence of 69.9% on customer satisfaction, while the remaining 30.1% is influenced by other variables that were not studied in this study.